STRATEGI PEMENANGAN PASANGAN IDZA PRIYANTI - NARJO (IJO) DALAM PEMILUKADA KABUPATEN BREBES 2012 - Alfiyan Dwi Noprianto; Suwanto Adhi; Susilo Utomo (Journal of Politic and Government Studies, 2013)
Brebes is one of the regency in Central Java that have conducted elections in 2012. The winner is the couple Idza Priyannti - Narjo. Victory of this couple is interesting to observe. First, look at the background of candidates who in fact had no political background to face with incumbent candidate Agung Widyantoro. Second, look at to the abung party support that he get by many of party coalition and the large parties in Brebes Regency, to face with Idza Priyanti who had supported by only some party. By the two reason above, interesting to know about political strategy to used by Idza Priyanti Narjo, so they can be the winner of election in Brebes Regency.The purpose of this study was to determine the strategies used by couples Idza Priyanti - Narjo so can obtain a majority vote in the Brebes General Election 2012. This study uses a qualitative analysis in descriptive analytical. The main data sources obtained from indepth interviews with several informants, Idza Priyanti and Narjo as the main actor, the bearer party PDIP and PKS and successful team, and literature of documents that relevant to this study.Based on the research, the strategy used by Idza Priyanti - Narjo, can be classified in two ways. First, the strategy that ijo used including job program, fight to people prosperous and 6 main pillar program and had the independent tim from this couple. Second, the strategy that propose party used including the solid party support and the strategy by succesful team, political marketing strategy and the effective campaign.Keywords: Winning Strategies, Election.